Down-regulation of type I interferon receptor sensitizes bladder cancer cells to vesicular stomatitis virus-induced cell death - Zhang, Kai-Xin; Matsui, Yoshiyuki; Hadaschik, Boris; Lee, Cleo; Jia, William; Bell, John C.; Fazli, Ladan; So, Alan I.; Rennie, Paul S. (International journal of cancer, 2010)
The intrinsic oncolytic specificity of vesicular stomatitis virus (VSV) is currently being exploited to develop alternative therapeutic strategies for bladder cancer and other cancers. Previously we reported that oncolytic VSV is a potent agent for intravesical treatment of high risk bladder cancer. We observed that VSV preferentially targeted bladder cancer cells resistant to type I interferon (IFN) treatment. The goal of the current study was to further elucidate the nature of the molecular defect of IFN signaling by which bladder cancer cells become susceptible to VSV infection. Using a tissue microarray composed of human bladder cancer cores, we observed that expression of type I IFN receptor (IFNAR) was decreased relative to normal bladder tissue. Advanced bladder cancers had even lower expression of IFNAR. We found that bladder cancer cells susceptible to VSV-induced lysis had low expression of IFNAR as well. We hypothesized that down-regulation of IFNAR in bladder cancer cells may be a molecular mechanism responsible for resistance to type I IFN treatment and sensitivity to VSV oncolysis. SiRNA knockdown of IFNAR indeed facilitated replication of VSV in cells previously resistant to VSV treatment. Blocking IFNAR with a neutralizing antibody showed a similar effect. Hence down-regulation of IFNAR in bladder cancer may be one of the primary molecular mechanisms for clinical IFN resistance. However, this also facilitates VSV replication and oncolysis in high risk bladder cancers and provides a basis for selecting bladder cancer patients for IFN or oncolytic VSV therapy in future clinical trials.